Engineering High-Affinity T Cell Receptor/ Cytokine Fusions for Therapeutic Targeting - Stone, Jennifer D.; Yin, Yiyuan; Mo, Min; Weber, K. Scott; Donermeyer, David L.; Allen, Paul M.; Mariuzza, Roy A.; Kranz, David M. (IntechOpen, 2012)
None